Editorial: ‘One City, Many Tales’: COVID-19, perception, and the importance of contextualization - Zhang, Xiaoling (SAGE Publications Ltd, 2021)
This introduction to the special issue summarizes the contributions from the five leading scholars in the field—their contribution to the conceptualization of such concepts as soft power, sharp power, image shaping, image reception, as well as methodological approaches. It highlights the importance of contextualizing their findings for a full understanding of the image of China in the media narratives examined. In doing so, the Introduction lays foundation for further investigations on the relationship between media coverage of health crisis and image construction as the world continues to fight against the virus.